1621 : a new look at Thanksgiving - Grace, Catherine O'Neill, 1950- (National Geographic Society, 2004)
Takes a fresh look at the Thanksgiving of 1621 as ninety Native-Americans shared five deer, corn, hominy grits, and stewed squash with fifty-two English people and talked diplomacy.